Using a genetic algorithm technique to reduce harmonics in gird-connected inverters - Tran , Quang Tho; Truong, Viet Anh; Le, Minh Phuong (Journal of Technical Education Science, 2016)
The penetration of distributed generation (DG) using renewable energy sources - solar and wind power - into grid systems is rapidly increasing worldwide. To limit harmonics of DGs, the increasingly stringent grid standards are imposed by utility companies to maintain grid stability. Increasing the switching frequency of SPWM in inverters is a popular method used in practice for reducing total harmonic distortion (THD); however, this increases switching losses. This paper proposes an SPWM technique with variable switching cycle for reducing the harmonics but without any increase in switching loss using a genetic algorithm technique. To validate the performance of the proposed technique, the results generated by the proposed technique are compared to those of the existing variable switching frequency methods.